PENGARUH KARAKTERISTIKPEKERJAAN, BEBAN KERJA, STRES KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK MADYA MEDAN - Siska Syahvitri (Universitas Islam Islam Sumatera Utara, 2020)
The problem in this research are: How does the effect of job characteristics on employee performance in Medan Intermediate Tax Service Office. How does work influence affect employee performance, how does work stress affect employee performance, how does motivation influence employee performance, how does work characteristics influence, burden work, work stress and motivation on employee performance. The proposed hypothesis is: Job characteristics have positive and significant effect on employee performance, workload has positive and not significant effect on employee performance, work stress has a positive and not significant effect on employee performance, motivation has a positive and significant effect on employee performance, Job characteristics, burden work, work stress and motivation have a positive and significant effect on employee performance at the Medan Intermediate Tax Service Office.